Ant-mimicking thrips of the genus Compsothrips Reuter from China(Phlaeothripidae, Idolothripinae) - Dang, Lihong; Guo, Fuzhen; An, Yiyan; Mound, Laurence A. (Zootaxa, 2023)
Species of Compsothrips are ant-mimics in body form and structure. In contrast to the predatory species of ant-mimicking Aeolothripidae, these species feed by ingesting fungal spores. Worldwide, there are 27 species listed in this genus, with three recorded here from China. Compsothrips tenebronus is here considered a new synonym of C. sinensis, and C. timur is newly recorded from China in Tibet. Furthermore, C. reticulates is redescribed, with details of the female given for the first time. An illustrated key is provided to the three species of Compsothrips from China.